2014
DOI: 10.1002/tesq.192
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating U.S. Undergraduates’ Attitudes Toward International Teaching Assistants

Abstract: Intelligibility problems between native speakers (NSs) and nonnative speakers (NNSs) of English are often attributed to some perceived inadequacy of the NNSs. This emphasis on the NNSs’ role in successful communication is highly problematic, given that intelligibility is a negotiated process between speaker and listener. In some cases, NSs have negative attitudes toward NNSs that impair their willingness to communicate with NNSs and to acknowledge proficient NNS speech. Thus, NS attitudes are also important fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 76 publications
2
34
0
Order By: Relevance
“…We hope that, rather than ignoring the possibility of language injustice because it is not easily observable, more researchers will be motivated by this discussion to conduct empirical investigations of its consequences, just as increasing awareness of other societal privileges has driven increases in empirical study on those. In the domain of spoken language, it has been demonstrated that interventions can reduce various biases against non-native speakers (Derwing, Rossiter, & Munro, 2002; Kang, Rubin, & Lindemann, 2015); similar interventions could prove useful for increasing the equity of academic publishing, but these cannot be done unless the nature and scope of linguistic disadvantage in publishing is measured and acknowledged. Above we have outlined two avenues of research that would be valuable: estimating the difference in effort (if any) that native versus non-native English speakers spend on academic publishing, and estimating the magnitude of implicit bias (if any) in reviewing.…”
Section: Discussionmentioning
confidence: 99%
“…We hope that, rather than ignoring the possibility of language injustice because it is not easily observable, more researchers will be motivated by this discussion to conduct empirical investigations of its consequences, just as increasing awareness of other societal privileges has driven increases in empirical study on those. In the domain of spoken language, it has been demonstrated that interventions can reduce various biases against non-native speakers (Derwing, Rossiter, & Munro, 2002; Kang, Rubin, & Lindemann, 2015); similar interventions could prove useful for increasing the equity of academic publishing, but these cannot be done unless the nature and scope of linguistic disadvantage in publishing is measured and acknowledged. Above we have outlined two avenues of research that would be valuable: estimating the difference in effort (if any) that native versus non-native English speakers spend on academic publishing, and estimating the magnitude of implicit bias (if any) in reviewing.…”
Section: Discussionmentioning
confidence: 99%
“…Similar concerns about the difficulties of teaching in English exist in relation to ITAs in North America (Kang, Rubin, & Lindemann, 2015). Two major differences, however, exist between EMI lecturers and North American ITAs.…”
Section: Literature Reviewmentioning
confidence: 94%
“…This is expressed in Kang & Rubin's (2009) statement that "listeners often hear what they expect to hear, rather than accurately perceive nonnative student speech" (Kang & Rubin, 2009: 451). Rubin (Kang, 2008, 2012;Kang & Rubin, 2009Kang et al, 2015;Rubin, 2012;Staples et al, 2014) measure a proclivity to engage in reverse linguistic stereotyping by measuring listener language attitudes towards speakers believed to be Euro-American native speakers in contrast to attitudes towards speakers believed to be "foreign" nonnative speakers.…”
Section: Perception Of Racementioning
confidence: 99%